RASopathies: unraveling mechanisms with animal models - Granton A. Jindal (Disease Models & Mechanisms, 2015)
RASopathies are developmental disorders caused by germline mutations in the Ras-MAPK pathway, and are characterized by a broad spectrum of functional and morphological abnormalities. The high incidence of these disorders (∼1/1000 births) motivates the development of systematic approaches for their efficient diagnosis and potential treatment. Recent advances in genome sequencing have greatly facilitated the genotyping and discovery of mutations in affected individuals, but establishing the causal relationships between molecules and disease phenotypes is non-trivial and presents both technical and conceptual challenges. Here, we discuss how these challenges could be addressed using genetically modified model organisms that have been instrumental in delineating the Ras-MAPK pathway and its roles during development. Focusing on studies in mice, zebrafish and Drosophila, we provide an up-to-date review of animal models of RASopathies at the molecular and functional level. We also discuss how increasingly sophisticated techniques of genetic engineering can be used to rigorously connect changes in specific components of the Ras-MAPK pathway with observed functional and morphological phenotypes. Establishing these connections is essential for advancing our understanding of RASopathies and for devising rational strategies for their management and treatment.